Surface modification of waste gypsum for use as additive filler of greencomposites based on poly(butylene adipate terephthalate) - Do, Van Cong; Mai, Duc Huynh; Nguyen, Huu Dat; Nguyen , Quang Minh; Tran , Huu Trung; Nguyen , Thi Thu Trang; Kieu , Thi Quynh Hoa; Nguyen , Vu Giang (Vietnam Journal of Science and Technology, 2025)
Using fillers to reinforce and improve the desired properties of polymer composite materials is the desire of researchers. In which, the dispersion ability, interaction and adhesion between fillers and polymer matrix are the key to determine the properties of the obtained materials. This study focuses on surface modification of waste gypsum particles with ethylene bis stearamide (EBS) to use it as a reinforcing filler for polybutylene adipate terephthalate (PBAT), a biodegradable polymer with many advantages such as high flexibility and good barrier properties. Using energy dispersive X-ray spectroscopy (EDX), thermogravimetric analysis (TGA) and scanning electron microscopy (SEM) images observation confirmed that the WGS granules were successfully modified with the suitable EBS content of 5 wt.%. Thanks to the modification, the processability, dispersion and adhesion of WGS to the PBAT matrix were improved, as results, the mechanical and thermal performances as well as hydrolytic resistance of obtained biocomposites was also enhanced.